Antibacterial and Anti-Inflammatory Potential of Chinese Medicinal Herbs: Lonicerae flos, Lonicerae japonicae flos, Scutellaria baicalensis Georgi, and Forsythia suspensa - Ming, Xu; Yin, Ma; Liyan, Wan (Natural product communications, 2022)
Chinese herbal medicine (CHM) represents a potent, safe, and efficacious reservoir of treatment options against an array of microbial infections and inflammatory diseases. It has a long history of positive clinical outcomes with minimal or no side effects while enhancing and bolstering the host's protection against infections. With its unique ability to prevent, treat, and manage a wide range of diseased conditions, CHM has been successfully practiced in China for thousands of years. In the modern medical era, where harsh therapeutic drugs and antimicrobial resistance (AMR) present a significant challenge, CHM warrants further exploration. The present review highlights and focuses on 4 major CHM-based herbs, that is, (Lonicerae flos [LF], Lonicerae japonicae flos [LJF], Scutellaria baicalensis Georgi [SBG], and Forsythia suspensa [FS]) in terms of their antibacterial and anti-inflammatory efficacies. A detailed literature survey was done by the team using a systematic electronic search from PubMed, Science Direct, Google Scholar, Research Gate, books, etc. This was followed by data collecting, pertinent data extraction, in-depth analysis, and composing the final review. Each herb has been discussed in detail describing its mechanism adopted and the bioactive components involved in alleviating bacterial infections and inflammatory damage. Further, proof of efficacy by detailing the major past studies and major findings has been discussed for each of the 4 herbs. This review will give the scientific community the opportunity to update their knowledge on the subject, which is crucial for heralding the process of bringing CHM-based medicines closer to clinical development given the area of alternative medicine's rapid advancements.